PENENTUAN PENERIMAAN PEGAWAI MENGGUNAKAN METODE PERBANDINGAN EKSPONENSIAL (MPE) - Muryono, Tupan Tri; Irwansyah, Irwansyah; Budiyantara, Agus (ISTEK WIDURI, 2020)
Human resources (HR) plays an important role for the sustainability of higher education therefore xyz universities in conducting the process of selection of employees requires a truly competent employee in their respective fields. The problem in this study is that the selection process of employees is still subjective not based on pure test results and there is no proper method in employee acceptance. The purpose of this research is to get the right staff according to the needs of the college. There are five criteria that will be used in this study are education, work experience, psychotest scores, age, and interview scores. The data collection methods used in this study are interviews, library studies, and observations. The research methods used are the Exponential Comparison Method (MPE) and for the calculation of mpe methods using the python programming language. The result of this study is that mpe method can be applied to determine the admission of employees at xyz college.